The Hadhrami Diaspora in Southeast Asia : identify maintenance or assimilation - Abu Shouk, Ahmed Ibrahim (E.J. Brill, 2009)
This volume originates from the proceedings of an international conference convened by the Department of History and Civilization, International Islamic University Malaysia, in collaboration with the Embassy of the Republic of Yemen, in Kuala Lumpur, from 26 to 28 August 2005. Twelve out of thirty-five papers presented at the conference have been reviewed, thoroughly revised and published in this volume. The introduction and the twelve chapters address the question of Hadhrami identity in Southeast Asia from various perspectives and investigate the patterns of Hadhrami interaction with